2014
DOI: 10.1080/10408398.2012.740102
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Degradation of Beta-casomorphins in Dairy Processing

Abstract: Milk proteins including casein are sources of peptides with bioactivity. One of these peptides is beta-casomorphin (BCM) which belongs to a group of opioid peptides formed from b-casein variants. Beta-casomorphin 7 (BCM7) has been demonstrated to be enzymatically released from the A1 or B b-casein variant. Epidemiological evidence suggests the peptide BCM 7 is a risk factor for development of human diseases, including increased risk of type 1 diabetes and cardiovascular diseases but this has not been thoroughl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 76 publications
(136 reference statements)
0
50
0
4
Order By: Relevance
“…Pretreatment heat can enhance existing health effects of bioactive peptides: Adjonu, Doran, Torley, and Agboola (2013) found that pretreatment at temperatures higher than 90°C enhanced ACE-inhibiting activity of a β-lactoglobulin fragment. Results of Jayatilake et al (2014) imply that treatment at low temperatures could also enhance the anti-inflammatory action of whey proteins, due to higher retention of immunoactive proteins and factors, such as immunoglobulins, lactoferrin, and growth factors (Nguyen et al, 2015). Other factors that could be important include the type of heat source: Gomaa (2010) found that microwave heating not only enhanced antioxidative activity of β-lactoglobulin hydrolysate, but the same hydrolysate also presented unique proteins, an indication that microwave treatment may have exposed new cleavage sites within the protein.…”
Section: Effect Of Thermal Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment heat can enhance existing health effects of bioactive peptides: Adjonu, Doran, Torley, and Agboola (2013) found that pretreatment at temperatures higher than 90°C enhanced ACE-inhibiting activity of a β-lactoglobulin fragment. Results of Jayatilake et al (2014) imply that treatment at low temperatures could also enhance the anti-inflammatory action of whey proteins, due to higher retention of immunoactive proteins and factors, such as immunoglobulins, lactoferrin, and growth factors (Nguyen et al, 2015). Other factors that could be important include the type of heat source: Gomaa (2010) found that microwave heating not only enhanced antioxidative activity of β-lactoglobulin hydrolysate, but the same hydrolysate also presented unique proteins, an indication that microwave treatment may have exposed new cleavage sites within the protein.…”
Section: Effect Of Thermal Processingmentioning
confidence: 99%
“…Several review papers list various health effects of bioactive peptides from foods of animal origin (Aneiros & Garateix, 2004;Bhopale, 2016;Lafarga & Hayes, 2014;Nguyen, Johnson, Busetti, & Solah, 2015;Udenigwe & Howard, 2013;Yu, Yin, Zhao, Chen, & Liu, 2014;Zambrowicz et al, 2015) and these characterized bioactive peptides have been incorporated into databases such as BIOPEP (Table S1). However, most of these databases cover peptides of specific length, origin, and/or health effect.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies clearly show that β-casomorphins opioid-like peptides are derived from β-casein [19][20][21][22][23][24][25][26] . β-Casomorphins are exogenous opioid peptides derivatives containing the common N-terminal amino acid sequence Tyr-Pro-Phe-Pro and have preferential μ-receptor agonistic activity [25] .…”
Section: Discussionmentioning
confidence: 99%
“…After mixing 500 µL octanol, 500 µL 0.9% NaCl or H 2 O and 10 microcurie 99m Tc labeled peptide in a vortex mixer for 1 min, they were centrifuged at 4.000 rpm. Low phase and upper phase radioactivity were counted in dose calibrator and phases were rationed and logarithm was calculated [22,24,25] . The lipophilicity was calculated using the formula logP = A0/Aw Besides, theoretical lipophilicity values were compared with experimental values using ACD chemsketch computer program (Table 2).…”
Section: -Determination Of Lipophilicitymentioning
confidence: 99%
See 1 more Smart Citation